Transverse sectioning in the evaluation of skin biopsy specimens from alopecic dogs. (12th October 2020) - Bond, R.; Hendricks, A.; Patterson‐Kane, J.; Stevens, K.; Brooks Brownlie, H. W.
Abstract : Objectives: Transverse sectioning of skin biopsy specimens has revolutionised assessment of human alopecia by demonstration of every hair in each specimen, allowing quantitative evaluation of follicular activity. Since only vertical sectioning is performed routinely in veterinary laboratories, we aimed to determine whether transverse sectioning was a valuable technique in assessment of canine alopecia. Methods: Paired vertical and transverse sections of biopsy specimens from 31 alopecic dogs were examined independently in triplicate in random order and blinded to previous diagnosis using a standard check‐list proforma. Assessments of key features (follicular activity [anagen/telogen], infundibular hyperkeratosis, sebaceous gland abnormalities, pigment clumping, dermal inflammation) by each sectioning method were compared. Results: In the 31 cases, (atrophic [n = 13], dysplastic [n = 12], inflammatory diseases [n = 6]), follicular inactivity scores (median, [lower‐upper quartile]) in transverse sections significantly exceeded those in vertical sections (transverse 4 [3‐5], vertical 3 [2‐4]). Agreement between the two sectioning planes was moderate for infundibular hyperkeratosis (kappa = 0.5210) and dermal inflammation (0.4351), fair for sebaceous gland abnormalities (0.3966) and pigment clumping (0.2197), but slight for follicular activity (0.1041). Vertical sectioning demonstrated diagnostically important epidermal pathology (n = 2) and dermal thinning (n = 3) whereas transverse sectioning enhanced assessment of hair growth phase (n = 11), follicular structure and architecture (n = 11), and focal luminal or mural folliculitides (n = 3). Clinical significance: Transverse sectioning confers significant benefits and complements traditional vertical sectioning in the histological assessment of canine hair follicle diseases, particularly when subtle abnormalities comprise distorted compound follicle architecture, hair cycle arrest or when relatively few adnexal structures are affected.